A research on leadership behaviors of nurse managers working in public hospitals - Nihal Ünaldı Baydın; İbrahim Topçu; Hanife Tiryaki Şen; Nimet Ateş; Binnur Erdem; Aytolan Yıldırım (Association of Nurse Managers, 2017)
INTRODUCTION: Leadership characteristics possessed by the nurse managers are highly significant with the quality of the nursing services. This study has been conducted for the purposes of identifying the demographic characteristics and perceived their leadership behaviors of the nurse managers working at the public hospitals. METHODS: The population of the study is descriptive type of the Ministry of Health in Turkey and the university hospitals of 100 beds or more employees consisted of executives nurses who staff. Without going on the choice of whole sample can be allowed to reach a total sample. The data obtained from a total of 741 individuals were included in the analysis. As a tool for data collection is used Nurse Manager Information Form and Leadership Behaviour Scale. RESULTS: The majority of nurse managers working in Ministry of Health hospitals participating in the study (93.7%), 42 years and over (41.7%), and that the nurse profession (87.7%), those who nurse managers, including the profession of midwife (12.3%), associate's degree level of education is (% 56.7), profession. Nurse managers, Leadership Behavior Scale the sum of the average score was 6.08 +- 0: 57, respectively, the highest average score from the first three sub-dimensions, the team game (6.51 +- 0.64), the process of tracking (6.40 +- 0.76), the viewer gain (6.37 +- 0.63) respectively. It was determined that there was a significant statistically difference in between average scores of nurse managers which were scored scale according to personal and professional variables of nurse managers. DISCUSSION AND CONCLUSION: It has been concluded that nurse managers working at hospital considered themselves as a leader, successful about team play, pursuing works done, mentoring respect and sympathy from staff but perceieved themselves inefficient about creating vision.